2022
DOI: 10.3390/jcm11144126
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Satisfaction, Compliance and Side Effects among Long-Term Orthokeratology Wearers

Abstract: Purpose: This study aims to assess the satisfaction, compliance, and side effects among the long-term orthokeratology (Ortho-K) users in a tertiary hospital in Taiwan and analyze the side effects and related risk factors. Methods: Children and their guardians were assessed using a structured and validated questionnaire inquiring about background information, wear and care behaviors, daily activities, satisfaction, and related concerns. Clinical information, including refractive data and side effects, was obtai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 31 publications
0
2
0
Order By: Relevance
“…108 With overnight orthokeratology, a parent may insert, remove, and clean the lenses, even in older children, which may introduce an inconvenience factor. 109 On the other hand, the cleaning and storage of lenses are obviated with daily disposable soft contact lenses. Contact lenses are an attractive option for active children, although, for swimmers, orthokeratology is more convenient.…”
Section: Summary and Other Considerationsmentioning
confidence: 99%
See 1 more Smart Citation
“…108 With overnight orthokeratology, a parent may insert, remove, and clean the lenses, even in older children, which may introduce an inconvenience factor. 109 On the other hand, the cleaning and storage of lenses are obviated with daily disposable soft contact lenses. Contact lenses are an attractive option for active children, although, for swimmers, orthokeratology is more convenient.…”
Section: Summary and Other Considerationsmentioning
confidence: 99%
“…Contact lenses will ultimately require more practitioner time, including insertion and removal training 108 . With overnight orthokeratology, a parent may insert, remove, and clean the lenses, even in older children, which may introduce an inconvenience factor 109 . On the other hand, the cleaning and storage of lenses are obviated with daily disposable soft contact lenses.…”
Section: Summary and Other Considerationsmentioning
confidence: 99%
“…38 Previous studies have shown that OK lenses were not effective to all myopia due to the problem of cost, comfort, corneal staining or other complications. 39 For patients with high myopia, high astigmatism or flat corneas, it was also difficult to fit OK lenses. 40 In comparison, the advantage of RLRL therapy is its effect on both premyopes and myopes with no astigmatism limit.…”
Section: Adverse Eventsmentioning
confidence: 99%